Interrogating the effects of carbon-dioxide (CO2) emissions on life expectancy in Nigeria: an ARDL approach (2024)
This study examines the relationship between CO2 emissions and life expectancy in Nigeria, employing an Autoregressive Distributed Lag (ARDL) model to analyse both short-run and long-run effects. The study utilises data spanning from 1986 to 2020, focusing on C02 emissions from different sources—solid, liquid, and gaseous fuels—alongside economic growth indicators and government health expenditures. The findings reveal that CO2 emissions from all sources negatively affect life expectancy in both the short-run and long-run analyses, with emissions from solid and liquid fuels showing particularly strong adverse effects. Conversely, the study finds that higher GDP per capita and increased government health expenditure significantly enhance life expectancy, acknowledging the critical role of economic development and health funding in improving public health outcomes. The study confirms the necessity for comprehensive environmental policies aimed at reducing pollution and promoting cleaner energy alternatives. Additionally, it highlights the importance of economic policies that foster growth and health sector investments, suggesting these as dual avenues for enhancing the well-being and longevity of the Nigerian population. This paper contributes to the existing literature by providing empirical evidence of the direct and indirect effects of environmental and economic factors on public health. It offers valuable insights for policymakers on the importance of integrated strategies that address both environmental sustainability and economic development toward improving life expectancy in developing countries like Nigeria.